Alternative bioherbicide based on Trichoderma koningiopsis: Enzymatic characterization and its effect on cucumber plants and soil organism. (September 2021) - Ulrich, Alessandro; Lerin, Lindomar Alberto; Camargo, Aline Frumi; Scapini, Thamarys; Diering, Naudio Ladir; Bonafin, Fábio; Gasparetto, Ilana Giachini; Confortin, Tássia Carla; Sansonovicz, Patricia Fátima; Fabian, Robson Luis; Reichert Júnior, Francisco Wilson; Treichel, Helen; et al.
Abstract: The work aimed to produce and characterize a biocompound based on Trichoderma koningiopsis ; to evaluate the phytotoxic and morphological effects on cucumber plants ( Cucumis sativus ) model, and to study the ecotoxicity of the bioproduct in earthworms. The biocompound was produced by submerged fermentation to obtain the crude extract (ECd), filtered solution with filter paper (FilP), and gauze (FilG). From the ECd, the activity of the enzyme's amylases, cellulases, lipases, and total peroxidases was determined, with three replicates. Among the evaluated enzymes, a high concentration of total peroxidases (44 U mL −1 ) was observed. The ECd, FilP, and FilG biocompound preparations were applied to cucumber plants, isolated, and combined with the commercial herbicide based on potassium glyphosate. The FilG treatment caused the control of up to 80% of the cucumber plants 15 days after application. However, when FilG was combined with the herbicide glyphosate potassium, there was total depigmentation of 95% of the leaves and mortality of more than 90% of the cucumber plants. In evaluating ecotoxicity with earthworms ( Eisenia andrei ), there was no mortality when the organisms were exposed to the biocompound preparations; however, 68% rejected the biocompound associated with commercial herbicide was observed. In this way, T. koningiopsis biocompound demonstrated the potential action as a bioherbicide, with relevant data for the agricultural sector, to search for alternative methods to reduce costs and promote food and environmental security. Highlights: The fungus T. koningiopsis is a potential bioherbicide The production of phytotoxic enzymes is increased in the T. koningiopsis -based bioherbicide The biocompound was highly toxic to a plant model in greenhouse conditions. T. koningi opsis compound combined with underdose of commercial herbicide controlled up to 100% of the cucumber plants. The biocompound was not toxic to earthworms, in the ecotoxicity test